Advances in mechanism and treatment strategy of cancer - Zeng, Ye (Cellular and Molecular Biology, 2018)
Cancer is one of the most serious diseases with high incidence and high mortality rate threaten human health and quality of life. The researches on mechanisms of cancer development and metastasis, and effective and reasonable treatment strategies are of great significance. The traditional treatments for tumors such as surgery, radiotherapy, and chemotherapy have some benefits, but many drawbacks such as drug-resistance and side-effects. With the emergence of new therapeutic methods such as tumor-targeted drugs and immune drugs, the survival of cancer patients is improved, but reports on cardiac damage caused by therapeutic drugs are increasing.